Projeto de reabilitação de duas casas burguesas do Porto - Ensaio de uma metodologia de intervenção - Carlos Emanuel Ferreira Nogueira (2017)
The present work consists in the realization of a rehabilitation project of twobourgeois houses in the historical center of Porto.From the analysis and interpretation of the pre-existence, we tried to constitutea response in the form of a project that is based on the analysis and test of themethodology of intervention in the construction system, developed by Teixeira(2013).The practical side is parallel to the analysis and theoretical investigation, sincethe case study motivates the reflection on the problems inherent to the rehabilitationof old buildings.